A CHANGE DETECTION AND RESOURCE-AWARE DATA SENSING APPROACHES FOR IMPROVING THE REPORTING PROTOCOL MECHANISM FOR MOBILE USER - annisaa sri indrawanti; Waskitho Wibisono (Faculty of Computer Science - Universitas Indonesia, 2015)
Update mechanism is an important process that relays information to the end-user by sending the data from the client to the server. There are several kinds of update mechanism that are used, one of them is reporting protocol. Reporting protocol sends the data from the client to the server continuously in a certain time interval. Reporting protocol occasionally sends the same information repeatedly to the end-user and sometimes the data aren’t needed by the end-user. This is an issue, because it can cause a large amount of bandwidth usage. In this research, we have developed an improvement of the reporting protocol mechanism for mobile user using change detection and resource-aware data sensing to minimize the bandwidth and resource usage. The improvement of reporting protocol that is implemented reduces frequency of data transfer with the prediction of the changes in user activity and position. The prediction is used as a trigger when the data is about to be sent. The results have shown that the adaptive reporting protocol could improve the performance of the overall reporting protocol. This is shown by the improvement of the bandwidth efficiency up to 36-97%, memory efficiency at 1.5-6% and battery efficiency at 7-13%.